IMPLEMENTASI PEMROGRAMAN PYTHON MENGGUNAKAN GOOGLE COLAB - Nazar, Ridwan (Universitas Mahakarya Asia, 2024)
Python is a programming language that is widely used by large companies and developers to develop various kinds of desktop, web and mobile-based applications. Apart from large companies and developers, Python is also widely studied among students and campuses, especially IT-based campuses. Learning programming is not easy, but it is not difficult either, depending on how you learn it, and how quickly you learn it. Learning programming can be done more easily by going through the basics of programming which are summarized in three basic structures, namely sequence, branching and repetition. The programming structure is written using an IDE (Integrated Development Environment). One of the IDEs (Integrated Development Environment) for Python programming is Google Colab (Google Colaboratory), which can be run on Windows, Linux and Mac operating systems. This article aims to make it easier to learn basic Python programming using Google Colab, starting from how to create Google Drive files and create notebooks, as well as Python programming on Google Colab based on programming algorithms. The method used is literature study and experiments. A literature study was carried out to examine basic programming concepts which are summarized in algorithms consisting of sequence algorithms, branching algorithms and looping algorithms. The experiment was carried out to try the algorithm code into a Python programmer which was implemented using Google Colab.